2022
DOI: 10.1001/jamanetworkopen.2022.20176
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prenatal Exposure to Endocrine-Disrupting Chemicals With Liver Injury in Children

Abstract: IMPORTANCE Prenatal exposures to endocrine-disrupting chemicals (EDCs) may increase the risk for liver injury in children; however, human evidence is scarce, and previous studies have not considered potential EDC-mixture effects. Furthermore, the association between prenatal EDC exposure and hepatocellular apoptosis in children has not been studied previously.OBJECTIVE To investigate associations of prenatal exposure to EDC mixtures with liver injury risk and hepatocellular apoptosis in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 66 publications
3
28
1
Order By: Relevance
“…Epidemiological studies have suggested that urinary phthalate metabolite concentrations are associated with elevated markers of liver injury, such as serum ALT AST, gamma-glutamyl transferase (GGT) and alkaline phosphatase (ALP), indicating the potential toxic effect of phthalate exposure on the liver. ( Yu et al, 2021 ; Midya et al, 2022 ). Animal experiments have also reported that DEHP exacerbates nonalcoholic fatty liver in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have suggested that urinary phthalate metabolite concentrations are associated with elevated markers of liver injury, such as serum ALT AST, gamma-glutamyl transferase (GGT) and alkaline phosphatase (ALP), indicating the potential toxic effect of phthalate exposure on the liver. ( Yu et al, 2021 ; Midya et al, 2022 ). Animal experiments have also reported that DEHP exacerbates nonalcoholic fatty liver in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Humans, even pregnant women and children are widely exposed to DEHP in everyday life via ingestion of food, inhalation, skin contact, and medical devices. Growing epidemiological evidence has highlighted the association between phthalate exposure and a higher risk for liver injury ( Yu et al, 2021 ; Midya et al, 2022 ). As an endocrine disrupting chemical (EDC), DEHP is reported to be toxic to rodent liver, leading to lipid metabolism disorder, liver injury and nonalcoholic fatty liver disease ( Chen et al, 2016 ; Zhao et al, 2020 ; Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of those participants aged 70 years or older, 71.7% had high PCB levels compared to only 2.2% of those aged under 30 years. A study of 1,108 mother–child pairs from six countries by Midya ( 72 ) discovered that prenatal exposure to PCBs is a potential risk factor for pediatric NAFLD, and were further associated with increased CK-18 levels (a novel marker of hepatocyte apoptosis and NAFLD). Notably, researchers have identified potential therapeutic targets for improving PCB-induced NAFLD, including the anti-fibrotic compound recombinant FGF21, which reduced the overexpression of hepatic lipocalin-2 (LCN2), a group of transporters of small lipophilic molecules that are upregulated in several liver diseases, and attenuated NAFLD ( 62 , 77 ).…”
Section: Relationship Between Nafld and Edcsmentioning
confidence: 99%
“…First, inspired by the correlation patterns of endocrine-disrupting chemicals from (Midya et al (2022a)),…”
Section: Simulation Setupmentioning
confidence: 99%